Immune response of rabbits immunized with outer membrane proteins (porins) of Salmonella dublin 51 - CHATURVEDI, G C; KAURA, Y K; MINAKSHI, MINAKSHI (The Indian Journal of Animal Sciences, 2013)
Porins complexed with polysaccharide of Salmonella dublin 51 used for immunization of rabbits proved nonÂ· toxic. Agglutinin titre ranged from 1:40 to 1:320 against '0' 9, 12 antigen. Titre against porins by dot-ELISA was 1:100-1 :400. Antiporins in the serum samples of 2 rabbits were demonstrable at 5 weekspostimmunizution bycounter-immunoelectrophoresis (Cm), while it was detected in the 4 rabbits at 6 weeks post-challenge before sacrifice by both immunodiffusion ami ClE. The immediatetype skin hypersensitivity reaction was 12.00. 15.00mm (skin thickness) at 6 hr (Peak skin reaction) post-antigen inoculution in the rabbits, at 5 weeks Post immunization. Skin biopsy collected at 6 hr (peak skin reaction) post-antigen inoculation revealed infiltration of neutrophils. The antiporin in the serum samples of all the rabbits were also deteoted by dot ELISA at 6 weeks post-challenge before sacrifice. The cell-mediated immune response (Icucocytemignllion inhibition and delayed type of skin hypersensitivity reaction) in the immunized rabbits was insignificant. The percentage protection of the immunized rabbits was 66.66% (statistically significant) against oral challenge.